INCREASING TEACHER COMPETENCY IN PREPARING HOTS-BASED TEACHING MATERIALS IN THE UPT SDN GRESIK ENVIRONMENT - Wardani, Imas Srinana; Achmad Fanani; Ida Sulistyowati; Via Yustitia; Bramianto Setiawan (Pasundan International of Community Services Journal (PICS-J), 2023)
Preparing HOTS-based teaching materials is a competency that teachers must have. Elementary school teachers are required to have the ability to create teaching materials that encourage students to be motivated in observing everything around them, asking questions, and thinking creatively and critically so that they can explore the competencies of elementary school students. The aim of holding this PPM is so that elementary school teachers in the Gresik area will increase their competence in preparing teaching materials, especially for preparing HOTS-based teaching materials. The method used is descriptive qualitative with instruments in the form of interview sheets, questionnaires, and documentation related to the implementation of community service or PPM. PPM participants consisted of 25 elementary school teachers in the Gresik area. As a result, after the PPM activities were carried out, the competency of elementary school teachers in preparing HOTS-based teaching materials increased. This can be seen from every aspect of making HOTS-based teaching materials that has been fulfilled, this is because the human resources of elementary school teachers in the Gresik area already have a profile that supports their competency abilities.